Relationship between Family Support and Medication Adherence Levels among Patients with Mental Disorders - Rizani, M. Dzaki Zimbbran; Sujiah, Sujiah; Rahman, Aulia (Genius Journal, 2026)
Introduction: Mental disorders remain a significant global health issue, affecting millions of individuals worldwide and posing serious challenges to overall well-being and quality of life. Family support plays a crucial role in improving treatment outcomes, particularly in enhancing medication adherence and reducing the risk of relapse among patients with mental disorders. Objective: This study aims to analyze the relationship between family support and medication adherence among patients with mental disorders at the Lampung Provincial Mental Hospital. Method: This quantitative, cross-sectional study investigated the relationship between family support and medication adherence among mental disorder patients. The study involved 348 family members and patients attending follow-up controls at the Mental Hospital Polyclinic in Lampung Province. Data analysis, utilizing univariate and bivariate methods with the chi-square test, yielded significant findings. Result: The results unequivocally demonstrate a strong, significant relationship between family support and medication adherence, evidenced by a p-value of 0.001 (p-value < 0.05). This indicates that a higher level of family support is directly associated with improved medication adherence among patients with mental disorders. In conclusion, robust family support is a critical factor in enhancing medication adherence. Conclusion: To effectively reduce relapses, often triggered by treatment fatigue, consistent and empathetic support from close family members is essential to sustain patient motivation throughout their recovery journey.